PELATIHAN KOMUNIKASI EFEKTIF MEDIA PEMBELAJARAN GOOGLE CLASSROOM BAGI GURU MAN 2 MODEL PEKANBARU - Fitria Mayasari; Desliana Dwita; Jupendri Jupendri; Jayus Jayus; Nazhifah Nazhifah; Khusnul Hanafi; Nolly Medya Putra (LPPM UMRI, 2019)
In today's digital era, teaching staff have many choices of interactive learning media that can support the learning process. One application that can help teachers realize effective communication between students and teachers is google classroom. The Google Classroom is a mixed learning platform that is intended for every educational scope that is intended to find a way out of the difficulties in making, sharing and classifying each paperless assignment. For this reason, there is a need for knowledge and skills about how effective communication can be done through innovative learning media based on Blended Learning (Google Classroom), so that the quality of teaching can be better. Therefore, dedication activities are carried out in MAN 2 Model on